A PCR-based sex determination method for possible application in caprine gender selection by simultaneous amplification of the Sry and Aml-X genes. - Phua, Alice Choon Yen; Abdullah, Ramli Bin; Mohamed, Zulqarnain (The Society for Reproduction and Development, 2003)
Sex determination of livestock is performed to achieve the objectives of livestock breeding programmes. Techniques for sex determination have evolved from karyotyping to detecting Y-specific antigens and recently to the polymerase chain reaction (PCR), which appears to be the most sensitive, accurate, rapid and reliable method to date. In this study, a PCR-based sex determination method for potential application in goat breeding programmes was developed. Primers were designed to amplify a portion of the X amelogenin gene (Aml-X) on the X chromosome to give a 300 bp product and Sry gene on the Y chromosome to give a 116 bp product. PCR optimization was performed using DNA template extracted from a whole blood sample of Jermasia goats (German Fawn x Katjang) of both sexes. It was possible to identify the sex chromosomes by amplifying both male- and female-specific genes simultaneously in a duplex reaction with males yielding two bands and females yielding one band. The Aml-X primer set, which served as an internal control primer, did not interfere with amplification of the Y-specific sequence even when a low amount of DNA (1 ng) was used. The duplex reaction subjected to a blind test showed 100% (14/14) concordance, proving its accuracy and reliability. The primer sets used were found to be highly specific and were suitable for gender selection of goats.